2019
DOI: 10.1021/acs.bioconjchem.9b00022
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment-Responsive Delivery of the Cas9 RNA-Guided Endonuclease for Efficient Genome Editing

Abstract: Successful and efficient delivery of Cas9 protein and gRNA into cells is critical for genome editing and its therapeutic application. In this study, we developed an improved supercharged polypeptide (SCP) mediated delivery system based on dithiocyclopeptide linker to realize the effective genome editing in tumor cells. The fusion protein Cas9-linker-SCP (Cas9-LS) forms positively charged complexes with gRNA in vitro to provide possibilities for gRNA delivery into cells. Under the microenvironment of tumor cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…After Cas9 initiates site-specific genomic DNA cleavage, endogenous repair at the targeted site leads to gene disruption or templated repair that can correct the underlying cause of genetic disorders . Until now, most of the CRISPR/Cas9 delivery systems had depended on physical or viral approaches that suffer from limited applicability and major immunological concerns. Most recently, synthetic delivery vehicles including cationic lipid nanoparticles, , gold nanoparticles, gold nanowires, DNA nanoclews, and other novel platforms have been reported for CRISPR/Cas9 delivery. Concurrently we have reported that metal organic frameworks (MOFs), namely, zeolitic imidazolate framework (ZIF-8), can serve as an excellent nonviral CRISPR/Cas9 delivery system . The huge surface area, tailored pore size, predesigned morphology, biocompatibility, and controlled degradability drive this class of propitious materials closer toward pharmaceutical and medical translation. Biological systems include hybrid metalloproteins and ion transporters which make hybrid carriers more plausible to address the needs for smart delivery.…”
mentioning
confidence: 99%
“…After Cas9 initiates site-specific genomic DNA cleavage, endogenous repair at the targeted site leads to gene disruption or templated repair that can correct the underlying cause of genetic disorders . Until now, most of the CRISPR/Cas9 delivery systems had depended on physical or viral approaches that suffer from limited applicability and major immunological concerns. Most recently, synthetic delivery vehicles including cationic lipid nanoparticles, , gold nanoparticles, gold nanowires, DNA nanoclews, and other novel platforms have been reported for CRISPR/Cas9 delivery. Concurrently we have reported that metal organic frameworks (MOFs), namely, zeolitic imidazolate framework (ZIF-8), can serve as an excellent nonviral CRISPR/Cas9 delivery system . The huge surface area, tailored pore size, predesigned morphology, biocompatibility, and controlled degradability drive this class of propitious materials closer toward pharmaceutical and medical translation. Biological systems include hybrid metalloproteins and ion transporters which make hybrid carriers more plausible to address the needs for smart delivery.…”
mentioning
confidence: 99%
“…To solve this drawback, they introduced a cleavable dithiocyclopeptide linker between Cas9 and SCP which contains a matrix metalloproteinase 2 (MMP-2) recognition site and an intramolecular disulfide bond (denoted Cas9-linker-SCP). 232 Free Cas9 proteins were sufficiently released from Cas9-linker-SCP via extracellular MMP-2 cleavage and subsequent intracellular GSH-induced disulfide break, which resulted in enhanced genome editing efficiency. In another study, Kim et al developed a carrier-free Cas9 RNP delivery strategy by engineering Cas9 protein containing a NLS and a low-molecular-weight protamine (LMWP).…”
Section: Reviewmentioning
confidence: 99%
“…However, few studies have been reported on CPP-mediated CRISPR component delivery at present. Moreover, both delivery efficiency and subsequent editing efficiency were usually at a low level of just 10-20% (Ramakrishna et al, 2014b;Yin et al, 2018b;Del'Guidice et al, 2018;Yin et al, 2019a). This likely stems from the indefinite mechanism of CPP internalization and requirement for extensive optimization for targeting each type of cargo and cell.…”
Section: Cell-penetrating Peptidesmentioning
confidence: 99%